Field testing and numerical investigation of streetscape vehicular anti-ram barriers under vehicular impact using FEM-only and coupled FEM-SPH simulations. Issue 2 (June 2016) - Yoo, Tae Kwang; Qiu, Tong; Reese, Lynsey; Rado, Zoltan
This article presents two field-scale crash tests of Streetscape Vehicle Anti-Ram barrier systems and LS-DYNA simulations to predict the global response of each system under vehicular impact. Tests 1 and 2 consisted of a five-post welded bus stop and a welded bollard, respectively; both were in a steel and concrete composite foundation embedded in compacted American Association of State Highway and Transportation Officials aggregate. Test 1 resulted in a P1 rating, where minimal foundation uplift and rotation were observed. Test 2 failed to result in a P1 rating, where significant foundation uplift, rotation, concrete cracking, and large deformation of surrounding soil were observed. For each test, two LS-DYNA models, namely, a finite element method–only model and a hybrid finite element method–smoothed particle hydrodynamics model, were created to predict the global response of the system. In the finite element method–only model, traditional finite element method approach was used for the entire soil region; in the hybrid finite element method–smoothed particle hydrodynamics model, the near-field soil region was modeled using the smoothed particle hydrodynamics approach, whereas the far-field soil region was modeled using the finite element method approach. For Test 1, both the finite element method–only model and the hybrid finite element method–smoothed particle hydrodynamics model were able to match the recorded global response of the system. For Test 2, however, the finite element method–only approach was not able to accurately predict the global response of the system; on the other hand, the hybrid finite element method–smoothed particle hydrodynamics approach was able to capture the global response including the bollard pullout, soil upheaval, and vehicle override. This research suggests that the hybrid finite element method–smoothed particle hydrodynamics approach is more appropriate in simulating the field performance of embedded structures under impact loading when large deformation of the surrounding soil is expected.